Factor Causing Gender Inequality in Residential Building Construction Projects: A Case Study of Bharatpur-11 - Dawadi, Gayatri; Bohara, Niraj (International Journal on Engineering Technology and Infrastructure Development, 2024)
It is found that women workers are suppressed in all the discipline and occupations of construction not only in Nepal but worldwide. In this paper, we review 32 major factor that are accumulated from the different past research to recognize the causes of gender inequality that anticipate women from seeking after careers within the development field. These 32 factors are developed into a questionnaire and distributed to construction workers, contractors, consultants and clients. Survey were created in five points Likert Scale and ranked by Relative Importance Indices (RII). The factor analysis found five top ranked factors for gender inequality in construction were career break after having a child due to unavailable of childcare facilities, lack of professional development training, lack of opportunity to participate in development training, lack of promotion opportunities, and an absence of female role model with RII 0.9551, 0.865, 0.863, 0.835 and 0.832 respectively. The perception between the different groups of respondents look considerably different as discerned from Spearman’s correlation coefficient. Government should therefore take a proactive role in reducing gender imbalance in the building industry.